Approximation of Hyperbolic Tangent Activation Function Using Hybrid Methods - Sartin, Maicon A.; Silva, Alexandre C. R. da [UNESP]; IEEE (Ieee, 2013)
Artificial Neural Networks are widely used in various applications in engineering, as such solutions of nonlinear problems. The implementation of this technique in reconfigurable devices is a great challenge to researchers by several factors, such as floating point precision, nonlinear activation function, performance and area used in FPGA. The contribution of this work is the approximation of a nonlinear function used in ANN, the popular hyperbolic tangent activation function. The system architecture is composed of several scenarios that provide a tradeoff of performance, precision and area used in FPGA. The results are compared in different scenarios and with current literature on error analysis, area and system performance.
Keywords: hyperbolic tangent; FPGA; activation function; Hybrid Methods